ANTIBIOGRAM ANALYSIS AND MOLECULAR CHARACTERIZATION OF MULTI-DRUG RESISTANT GENES (TETK AND GYRA) OF STAPHYLOCOCCUS AUREUS ISOLATED FROM DIABETIC FOOT ULCERS PATIENTS IN PESHAWAR - Khan, Kamran; Ullah, Aman; Haq, Ihtisham UL; Khiam, Omer; Khan, Zaryab; Khan, Musa (International Journal of Pharma and Bio Sciences, 2026)
DFUs are one of the frequent complications of diabetic patients frequently resulting in the emergence of bacterial infections that make treatment difficult. The aim of this research was aimed at determining the antibiogram and molecular characterization of multidrug-resistant (MDR) genes, namely tetK and gyrA, in Staphylococcus aureus that was isolated on DFU patients in Peshawar, Pakistan. Sixty wound samples were taken out of DFU patients of Lady Reading Hospital, where more than 70% of respondents were males. Bacterial identification was done using biochemical tests (catalase and coagulase) and the samples were grown on the Mannitol Salt Agar (MSA). The Kirby-Bauer disc diffusion was utilized to identify the antibiotic susceptibility and PCR was done to identify the tetK and gyrA resistance genes. These findings indicated that rates of resistance to popular antibiotics were high with 100 percent resistance to ampicillin (100%), penicillin G (93%), and erythromycin (83%), with intermediate rates of resistance to tetracycline and ciprofloxacin. Further, the proportion of methicillin-resistant S. aureus (MRSA) and oxacillin-resistant of the isolates was 48 and 83 percent respectively. Molecular testing confirmed the existence of gyrA gene in 15 samples and tetK gene in 14 samples in which the two genes were important in antibiotic resistance. To sum up, the present paper highlights the increasing problem of antibiotic resistance to DFU infection. It highlights that persistent molecular monitoring and individualized treatment approaches should be used to provide effective treatment of infections among diabetic individuals.